Atypical Microbiological Feature of Infectious Endophthalmitis on Jeju Island: A 10-Year Study at a Single Tertiary Referral Center - Joong Hyun Park; Dong Yoon Kim; Ahnul Ha; Dae Joong Ma; Hye Jin Lee; Jinho Jeong; Jin Young Kim (Journal of Ophthalmology)
Background. To analyze the microbiological causes of infectious endophthalmitis on an isolated island over ten years. Methods. A retrospective review of the medical records of 49 eyes clinically diagnosed with infectious endophthalmitis between January 2009 and December 2018 was done. The subjects were recruited from a single tertiary referral center on Jeju Island. The baseline characteristics of all subjects were investigated, and a culture examination was performed. The isolated pathogens were analyzed to determine how their microbiological features differed from those in regions with different geographical conditions. Results. Of the 49 eyes, causative microorganisms were identified in 27 eyes (55.1%). Bacteria were found in 24 cases and fungi in 3 cases. Among the exogenous causes, Staphylococcus species (Staphylococcus aureus, S. epidermidis, and S. hominis) were the most common pathogens (7 cases). Achromobacter xylosoxidans was the second most common causative pathogen (4 cases) followed by Moraxella species (3 cases). The most frequent endogenous origin was due to Klebsiella pneumoniae (6 cases). The subjects were divided into two groups according to the treatment results and analyzed for predisposing factors related to visual outcomes. The presence of diabetes mellitus (P = 0.038) and initial visual acuity (P ≤ 0.001) were significant predisposing factors for visual outcomes. Conclusion. The causative microorganisms of endogenous endophthalmitis on Jeju Island were not different from those reported previously. However, isolated exogenous microorganisms were different from those reported in other studies from inland areas. A high incidence and atypical clinical features of Achromobacter xylosoxidans and Moraxella in exogenous endophthalmitis were observed, reflective of the distinct climatic features of Jeju Island: high humidity and temperature. Therefore, considering the causative microorganisms of exogenous endophthalmitis, it may be assumed that the causative microorganisms of exogenous endophthalmitis and its clinical manifestations differ according to the region.